The assessment of studies’ effectiveness as a reflection of achieved competencies in educational context at higher university settings using action research - Strukčinskienė, Birutė; Bartusevičienė, Inga (Social Welfare: Interdisciplinary Approach, 2018)
The aim of the study was to investigate the peculiarities of periodic assessment of student achievements, as a factor influencing effectiveness of studies, from the point of view of acquired competencies. For this study, action research was applied, and group discussion method was used. The study was performed at higher university education settings. The results of the presented research revealed the positive influence of the periodic assessment of the student achievements on the effectiveness of studies.